Towards control of the global HIV epidemic: Addressing the middle-90 challenge in the UNAIDS 90–90–90 target - Iwuji, Collins; Newell, Marie-Louise (PLOS Medicine, 2017)
In a Perspective, Collins Iwuji and Marie-Louise Newell discuss early findings from Richard Hayes and colleagues' PopART study on HIV testing and treatment.